Meningkatkan Motivasi Belajar Akidah Akhlak Melalui Pembelajaran Berbasis Teknologi pada Siswa Sekolah Menengah - Rahayu, Sri; Dwianti, Ririn (PTK: Jurnal Tindakan Kelas, 2025)
This research is motivated by the low motivation of students to learn in the subject of faith and morals, so it is considered necessary to innovate fun learning media in the learning process. The purpose of this study is to determine the effectiveness of technology-based learning in increasing students' learning motivation. This type of research is classroom action research with a quantitative approach. This research was conducted at MAN 1 Bone from October 1 to November 12, 2024. The subjects of this study were 36 students in class X-1. This research was conducted in 2 cycles, each of which followed several stages of classroom action research, namely planning, action, observation, and reflection. The data collection techniques used in this study were observation, tests and interviews. The data analysis technique used was descriptive statistical analysis techniques. The results of the study showed that in the pre-cycle the average learning motivation was 49%. In cycle I it became 67% and increased significantly in cycle II with a percentage of 89%. Thus, it can be concluded that technology-based learning can increase students' learning motivation in class X-1 MAN 1 Bone in the subject of faith and morals in the 2024/2025 academic year.